2022
DOI: 10.1002/smtd.202200916
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Thermal Decomposition Method to Produce Magnetic Nanoparticles with Ultrahigh Heating Efficiency for Systemic Magnetic Hyperthermia

Abstract: Due to the limited heating efficiency of available magnetic nanoparticles, it is difficult to achieve therapeutic temperatures above 44 °C in relatively inaccessible tumors during magnetic hyperthermia following systemic administration of nanoparticles at clinical dosage (≤10 mg kg−1). To address this, a method for the preparation of magnetic nanoparticles with ultrahigh heating capacity in the presence of an alternating magnetic field (AMF) is presented. The low nitrogen flow rate of 10 mL min−1 during the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…To improve its aqueous dispersibility, circulation time in the blood, and passive accumulation in inflamed tissue, the IRAK 4 inhibitor, PF‐06650833 ( Figure b), was encapsulated in the hydrophobic core of a poly(ethylene glycol)‐block‐poly(‐caprolactone) (PEG‐PCL)‐based nanocarrier using a solvent evaporation approach. [ 14 ] Numerous preclinical studies demonstrated that PEG‐PCL‐based nanoparticles hold great potential for drug delivery due to their safety, biocompatibility, and ability to effectively transport hydrophobic payloads following systemic administration. [ 15,16 ] PEG and PCL are biocompatible and nontoxic materials approved for biomedical uses in humans by the US Food and Drug Administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve its aqueous dispersibility, circulation time in the blood, and passive accumulation in inflamed tissue, the IRAK 4 inhibitor, PF‐06650833 ( Figure b), was encapsulated in the hydrophobic core of a poly(ethylene glycol)‐block‐poly(‐caprolactone) (PEG‐PCL)‐based nanocarrier using a solvent evaporation approach. [ 14 ] Numerous preclinical studies demonstrated that PEG‐PCL‐based nanoparticles hold great potential for drug delivery due to their safety, biocompatibility, and ability to effectively transport hydrophobic payloads following systemic administration. [ 15,16 ] PEG and PCL are biocompatible and nontoxic materials approved for biomedical uses in humans by the US Food and Drug Administration.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology, hydrodynamic size, polydispersity index, and surface charge of the resulting IRAK4 NC and VCAM1‐IRAK4 NC were evaluated by following the previously reported methods. [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local increase in heat can be used to induce cancer cell death, as well as the triggered release of the loaded drug. 93,94 Silica (SiO 2 ) NPs (SNPs) are also attractive for drug delivery as not only their size and shape, but also their porosity and the chemical properties of their surfaces can be controlled, which gives them the ability to store and release both hydrophilic and hydrophobic drugs. [95][96][97] Inorganic NPs are commonly produced by chemical methods (such as chemical reduction) to induce NP precipitation.…”
Section: Inorganic Npsmentioning
confidence: 99%
“…Numerous reports suggest that nanoparticles have the potential to improve conventional therapeutic (e.g., chemotherapy) and imaging (e.g., MRI) modalities for cancer detection and treatment [ 1 ]. Moreover, nanomaterials allow for the further development of novel experimental treatments and imaging strategies, including photothermal therapy, magnetic hyperthermia, and photoacoustic imaging [ 2 , 3 , 4 , 5 ]. In addition, although to a lesser extent, nanoparticle-based imaging and treatment modalities have been explored for other non-malignant diseases and disorders, such as ectopic pregnancy, endometriosis, muscle atrophy and several more [ 6 , 7 , 8 ].…”
mentioning
confidence: 99%